Little brother - Doctorow, Cory. (New York : Tor, 2010)
Interrogated for days by the Department of Homeland Security in the aftermath of a major terrorist attack on San Francisco, California, seventeen-year-old Marcus is released into what is now a police state, and decides to use his expertise in computer hacking to set things right.
"A Tom Doherty Associates book."
Includes bibliographical references (p. [375]-380).
School Library Journal starred
Wilson's Junior High School
Wilson's Senior High School
Booklist starred, April 2008
Keywords: United States. -- Dept. of Homeland Security -- Juvenile fiction; United States. -- Dept. of Homeland Security -- Fiction; United States. -- Dept. of Homeland Security -- Fiction; Civil rights -- Juvenile fiction; Counterculture -- Juvenile fiction; Hackers -- Juvenile fiction; Terrorism -- Juvenile fiction; Civil rights -- Fiction; Counterculture -- Fiction; Hackers -- Fiction; Terrorism -- Fiction; Civil rights -- Fiction; Computer hackers -- Fiction; Counter culture -- Fiction; Terrorism -- Fiction; San Francisco (Calif.) -- Juvenile fiction; San Francisco (Calif.) -- Fiction; San Francisco (Calif.) -- Fiction